2010
DOI: 10.2169/internalmedicine.49.3634
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Cystoides Intestinalis Induced by the Alpha-glucosidase Inhibitor Miglitol

Abstract: Pneumatosis cystoides intestinalis (PCI) is a rare condition in which pneumocysts develop in the submucosa or subserosa of the colon. We report herein a case of PCI induced by the alpha-glucosidase inhibitor (αGI) miglitol. There have been 9 recorded cases of PCI induced by other αGIs, but this is the first report of miglitol causing PCI. The PCI lesions in our case were smaller than those induced by voglibose or acarbose. The possibility of PCI should be considered in diabetic patients on αGI therapy who comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Bacterial overgrowth and bowel distension are observed in this condition, which can lead to elevated intraluminal pressure and force gas into the intestinal walls (6,19). Bacterial infection has also been proposed to either damage the intestinal wall with subsequent intramural penetration of gas or produce gas, which then penetrates into the gut wall (15). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial overgrowth and bowel distension are observed in this condition, which can lead to elevated intraluminal pressure and force gas into the intestinal walls (6,19). Bacterial infection has also been proposed to either damage the intestinal wall with subsequent intramural penetration of gas or produce gas, which then penetrates into the gut wall (15). …”
Section: Discussionmentioning
confidence: 99%
“…Bacterial overgrowth and increased intraluminal production of hydrogen may cause a breakdown in mucosal integrity and gas leakage into the bowel wall and peritoneal cavity (18). Several drugs, particularly α-GI, have been reported to induce PCI development (13-15). Use of α-GI causes flatulence, because absorption of carbohydrates by the colon is suppressed, and intestinal bacteria then generate a large volume of gas through carbohydrate fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, prescriptions of these drugs in Japan account for 98% of total sales of voglibose and 34% of those for acarbose (3). Providing conservative treatment after discontinuing the alpha-glucosidase inhibitor generally leads to the complete resolution of PI within 28 days (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PCI in diabetic patients is highly associated with the use of α-glucosidase inhibitors as well as other secondary causes [18]. Kojima et al suggested that carbohydrates are fermented by normal intestinal flora after their intestinal absorption has been inhibited by α -glucosidase inhibitors [18].…”
Section: Discussionmentioning
confidence: 99%